DOCSIS :Manual de Referencia - Suter,Tito; Vogt, Ada; Chávez Flores, Alejandra; Rollan; Gloria; Cassanello, Alicia; Gutiérrez, Elsa (Comisión Nacional de Energía Atómica (CNEA), 1988)
Fil:Suter,Tito Comisión Nacional de Energía Atómica (CNEA). República Argentina